The fight against money laundering - Johannes Dumbacher (Intereconomics, 1995)
During the past few years a new consciousness has emerged with regard to the question of money laundering, and new laws and mechanisms to combat it have been developed. The Financial Action Task Force on Money Laundering was established at the 15th World Economic Summit in Paris in July 1989. What activities have been developed so far by this and other international initiatives? What further steps must be taken?
Keywords: 330; Crime Prevention